Does Citizen Science Bring "Power to the People"? Evaluating a Remote Mapping Project to Identify Best Practices for Positive Impact on Volunteers. (6th February 2023) - Leonard, Alycia; Wheeler, Scot; McCulloch, Malcolm
A core tenet of citizen science is mutual benefit to the professional researcher and the citizen scientist. While the impacts on the citizen scientist are often implicitly assumed to be positive, this is infrequently studied directly. Here, we evaluate the impacts of the Power to the People remote mapping citizen science project on volunteers to explore best practices for positive impact. We analyze beta feedback collected before project launch, discussion board posts made during the project, an end-of-project evaluation survey, and mapping data generated during the project. We found that this project attracted a diverse global community who were motivated to contribute to research with the potential to create real-world impact. 87% of respondents had a "good" or "excellent" experience with the project, and 66% learned something by participating. Best-practices identified through this evaluation are to: (1) account for the intersectionality of contributor demographics; (2) emphasize project interdisciplinarity and real-world impact potential; (3) provide learning opportunities at multiple levels of depth; (4) remember that the most vocal contributors do not represent the entire community; and (5) evaluate data quality regularly to identify silent issues.